Data quality and information loss in standardised interpolated path analysis: Quality measures and guidelines - Annika Lenz; Muhammed Kaya; Philipp Melzer; Andreas Schmid; Josepha Witt; Mareike Schoop (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2019)
Standardised interpolated path analysis (SIPA) is a method to investigate negotiation processes making different negotiation histories comparable. Due to its interpolation approach, researchers employing SIPA must take data quality and potential information loss into account to maximise the method's explanatory power. This paper presents quality measures and applies them to two negotiation datasets for deriving meaningful boundaries. Using these quality measures enables researchers to compare SIPA across segmentations, variables, and datasets also providing outlier analysis.
urn:nbn:de:bsz:100-opus-16471
Keywords: 330; Electronic Negotiation; Negotiation process; Phase analysis